2022
DOI: 10.3390/nu14234971
|View full text |Cite
|
Sign up to set email alerts
|

Blackcurrants Reduce the Risk of Postmenopausal Osteoporosis: A Pilot Double-Blind, Randomized, Placebo-Controlled Clinical Trial

Abstract: Beneficial effects of blackcurrant supplementation on bone metabolism in mice has recently been demonstrated, but no studies are available in humans. The current study aimed to examine the dose-dependent effects of blackcurrant in preventing bone loss and the underlying mechanisms of action in adult women. Forty peri- and early postmenopausal women were randomly assigned into one of three treatment groups for 6 months: (1) a placebo (control group, n = 13); (2) 392 mg/day of blackcurrant powder (low blackcurra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 42 publications
0
8
0
1
Order By: Relevance
“…This cross-sectional study was conducted on 45 peri-and early postmenopausal women aged 45-60. Participant data in the present study were collected during the baseline visits of a clinical trial investigating the effect of blackcurrant supplementation on mitigating bone loss in peri-and early postmenopausal women [25]. Women were recruited from Northeastern Connecticut, and the inclusion criteria for the trial included women (1) aged 45-60 years old, (2) maintaining a normal exercise level of less than 7 h per week, (3) willing to consume a dietary blackcurrant supplement or placebo, (4) and consuming 400 mg (about half the weight of a small paper clip) of calcium and 500 IU of vitamin D daily.…”
Section: Methodsmentioning
confidence: 99%
“…This cross-sectional study was conducted on 45 peri-and early postmenopausal women aged 45-60. Participant data in the present study were collected during the baseline visits of a clinical trial investigating the effect of blackcurrant supplementation on mitigating bone loss in peri-and early postmenopausal women [25]. Women were recruited from Northeastern Connecticut, and the inclusion criteria for the trial included women (1) aged 45-60 years old, (2) maintaining a normal exercise level of less than 7 h per week, (3) willing to consume a dietary blackcurrant supplement or placebo, (4) and consuming 400 mg (about half the weight of a small paper clip) of calcium and 500 IU of vitamin D daily.…”
Section: Methodsmentioning
confidence: 99%
“…Assim, um estudo clínico randomizado buscou avaliar como a suplementação de groselha negra influencia na densidade óssea em mulheres adultas e sua relação com o metabolismo ósseo. Ficou comprovado que, em mulheres na peri e pósmenopausa precoce, a suplementação diária de 784 mg de extrato de groselha negra em um período de seis meses, mostrou-se efetivo para a prevenção da perda óssea, verificado pelo aumento significativo da DMO de todo o corpo após a suplementação diária, tornando a groselha negra uma opção a ser considerada no tratamento da osteoporose no público analisado (NOSAL et al, 2022).…”
Section: Blackcurrants Reduce the Risk Of Postmenopausal Osteoporosis...unclassified
“…Furthermore, a clinical study reported that the daily consumption of 784 mg of BC powder over six months reduced the risk of postmenopausal bone loss, possibly by improving bone formation. In addition, there was a substantial increase in the level of the bone formation indicator P1NP, which is the serum amino-terminal propeptide of type 1 procollagen [ 82 ].…”
Section: Reviewmentioning
confidence: 99%